Pain and Opioid Use: Evidence for Integrating Acupuncture Into Treatment Planning - Elizabeth Sommers PhD, MPH, LicAc; Sivarama Prasad Vinjamury DAOM, MD (Ayurveda); Jennifer Noborikawa DACM (SAGE Publishing, 2021)
The epidemics of pain and opioid use pose unique challenges. Comprehensive approaches are required to address minds, bodies and spirits of individuals who live with pain and/or opioid use. The lack of an effective "quick fix" for either condition necessitates developing effective, innovative and multi-disciplinary avenues for treatment. This analytic article reviews epidemiological and demographic factors associated with pain and with opioid use and additional challenges posed by the Covid-19 epidemic. Several large-scale studies and meta-analyses have examined the role of acupuncture as a nonpharmacological approach to pain management as well as a component of comprehensive strategies to address opioid use disorder. We review and describe these in the context of safety, effectiveness, access and cost-related factors. With one in four U.S. hospitals as well as 88% of Veterans Health Administration facilities incorporating acupuncture, the feasibility of mobilizing and scaling up these treatment resources is being developed and demonstrated. We also identify potential facilitators and barriers to implementing acupuncture treatment. As part of a multi-disciplinary approach to pain management and/or opioid use disorder, we suggest that integrating acupuncture into treatment protocols may represent a viable strategy that is based on and consistent with public health principles.